STRUKTUR DAN NILAI-NILAI DALAM TRADISI BUKOBA PANGLIMO AWANG MASYARAKAT PASIR PENGARAIAN - Misra - Nofrita (STKIP ROKANIA, 2021)
Koba Panglimo Awang is one of the oral traditions in Pasir Pengaraian, Rokan Hulu. Where, the existence of this tradition has begun to decrease its demand and its fragrance. For this reason, research is needed. To examine more deeply about Panglimo Awang koba. The purpose of this study was to describe the structure and values ​​of education contained in Koba Panglimo Awang. Data collection is done through two stages. The first stage is the recording stage of Bukoba oral literature. Informant's speech about Bukoba's oral literature is recorded using a recording device. The second stage is collecting data about the storytelling environment and analyzing the recorded data. The results of this study indicate that First, the structure in Koba Panglimo Awang is there, theme, characterization, plot, setting and message. Second, the educational values ​​contained in Koba Panglimo Awang are religious values, such as sincere, and grateful and moral values